2011
DOI: 10.1563/aaid-joi-d-10-00022.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Delayed Implant Placement vs Immediate Implant Placement Using Resonance Frequency Analysis: A Pilot Study on Rabbits

Abstract: Ten identical implants were equally divided into 2 groups. In the immediate placement (control) group, implants were placed immediately following osteotomy preparation, and in the delayed placement (test) group, implants were placed 2 weeks following osteotomy preparation, in rabbit femurs. Implant stability quotient values for both groups were measured using resonance frequency analysis immediately following placement and at day 40. Results were statistically analyzed and indicate that delayed placement of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Haas et al reported that immediate implant placement was more timee cient compared to delayed placement and could be a more aesthetic treatment option but did not show the same success rate as delayed placement [29]. In addition, Kunnekel et al found that osseointegration in delayed implantation occurred much faster than did that of immediate implantation according to resonance frequency analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Haas et al reported that immediate implant placement was more timee cient compared to delayed placement and could be a more aesthetic treatment option but did not show the same success rate as delayed placement [29]. In addition, Kunnekel et al found that osseointegration in delayed implantation occurred much faster than did that of immediate implantation according to resonance frequency analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Haas et al reported that immediate implant placement was more time-efficient compared to delayed placement and could be a more aesthetic treatment option but did not show the same success rate as delayed placement [ 30 ]. In addition, Kunnekel et al found that osseointegration in delayed implantation occurred much faster than did that of immediate implantation according to resonance frequency analysis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the QUS device was different since the ultrasonic probe was manually positioned on the implant abutment screw, leading to reproducibility issues, whereas a controlled insertion torque is introduced in the present study. Moreover, the relationship between the ISQ and BIC values have also been previously investigated (19)(20)(21)(22)(23)(45)(46)(47)) (see subsection 4.3) but none of these studies considered QUS measurements. The present study shows that QUS measurements (i) are better correlated to BIC values and (ii) have lower errors compared to RFA measurements.…”
Section: Originality Of the Studymentioning
confidence: 99%
“…Second, uncertainties on the estimation of BIC values was high because (i) only two BIC measurements could be realized for each implant and (ii) BIC measurements were realized on 2D histological sections, and can therefore only approximate actual BIC values on the entirety of the 3D implant. Third, a relatively low number of rabbits was considered herein, which is justified by ethical reasons and because it corresponds to the range of sample numbers used in previous studies using the Osstell device (15,22). Studies with more animals should be performed in the future.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation